Production, Optimization And Spectroscopic Studies Of Hyaluronic Acid Extracted From Streptococcus pyogenes - Saranraj, P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Hyaluronic acid (HA), a naturally occurring glycosaminoglycan, offers many unique advantages as a building block for biomaterials. Two different strains of Streptococcus pyogenes (442 & 1926) were obtained from MTCC and characterized. Optimization study for Hyaluronic acid production was carried out at different pH and different glucose concentration. Mutation studies were also carried as a mean for improving the Hyaluronic acid production. Hyaluronic acid compounds were qualitatively analyzed through HNMR spectroscopy. The Hyaluronic acid capsule of the two strains were quantified spectrophotometrically using stains all assay method. Based on the optimization study at different pH the maximum yield of Hyaluronic acid was obtained at pH 6.9. The yields of Hyaluronic acid from were Streptococcus pyogenes (442 & 1926) parallelly increases with increase in glucose concentration. The maximum Hyaluronic acid production was observed at 1% glucose concentration from Streptococcus pyogenes 442 marked under optimized pH 6.9. The production gradually increases due to improved energy yield. Mutation, with UV rays improves Hyaluronic acid production from Streptococcus pyogenes (marked 442) after 10 minutes of exposure. UV mutation produces positive effect on HAS gene (hyaluronats synthase gene). But the decline in the production of Hyaluronic acid was observed with Ethidium bromide treated calls. Since the survival rate of the bacteria is usually about 0.1% with chemical treatment. All three variable pH, glucose concentration and mutation have a major effect on the production of Hyaluronic acid by Streptococcus pyogenes (442 & 1926).